Antifungal edible coatings to control Alternaria black spot and maintain the quality of 'Rojo Brillante' persimmon during cold storage - Fernández-Catalán, Asunción; Palou, Lluís; Taberner, Verònica; Grimal, Amparo; Argente-Sanchis, Maricruz; Pérez-Gago, María B. (ISHS, 2022)
Spain is the second persimmon producing and main exporting country in the world, and ‘Rojo Brillante’ is the most important cultivar. Nowadays, the main interest of the Spanish persimmon industry is to extend the marketing period to reach off-season markets and technologies such as 1-methylcyclopropene in combination with cold storage are being used to reduce chilling injury and maintain fruit firmness. However, ‘Rojo Brillante’ persimmon is quite susceptible to postharvest Alternaria black spot, caused by Alternaria alternata.